Cell-autonomous action of Slit2 in radial migration of cortical projection neurons - Jiang, Tian; Niu, Guozhen; Wu, Chunping; Tu, Xiaomeng; Xiao, Jian; Li, Xue; Chen, Jie-Guang; Cao, Huateng (Frontiers in Molecular Neuroscience, 2024)
Neuronal radial migration is a fundamental process for cortical development, the disruption of which causes neurological and psychiatric dysfunctions. SLIT2 plays diverse functions in brain development and is a well-known axon guidance molecule. In this study, we investigated the radial migration of projection neurons in the developing cerebral cortex by in utero knockdown (KD) of Slit2 in mice. KD of Slit2 did not interfere with the neurogenesis and fate-determination but led to the accumulation of the transfected cells in the intermediate zone (IZ), suggesting that the expression of Slit2 is crucial for the radial migration of the cortical neurons. KD of Slit2 hindered the transition of cells from a multipolar to a bipolar shape, which is necessary for glia-guided locomotion. Interestingly, reducing Slit2 did not affect the migration of neighboring untransfected cells, indicating a cell-autonomous action by SLIT2. In addition, the action of SLIT2 KD was mimicked by a dominant negative mutant of ROBO2, a canonical membrane receptor of SLIT2, supporting that SLIT2 acted locally as a secretory molecule. Our results suggest that SLIT2 is indispensable for the radial migration of cortical neurons through an autocrine signaling mechanism.